Associação entre a qualidade da dieta de crianças e adolescentes com Diabetes mellitus tipo 1 e seus respectivos cuidadores - Valiati, Mariana (2017)
Background: The dietary treatment of Type 1 Diabetes Mellitus (T1D) is primordial in the prevention of classic complications of this disease. Although current literature suggests that the family diet influences children's eating patterns without the disease, little is known about the association of diet quality of children and adolescents with diabetes and their caregivers. Objective: Verify the association between the quality of the diet of children and adolescents with T1D and their caregivers. Methods: This cross-sectional study was conducted with 48 children and adolescents with T1D and their caregivers, and 46 children and adolescents without diabetes with their caregivers. Three dietary reminders were collected to calculate the quality of the diet, which was evaluated by the Revised Diet Quality Index (IQD-R) validated for the Brazilian population. Generalized linear models (GZLM) adjusted for confounding factors were used to evaluate the effect of T1D on the quality of the diet of caregivers and children and adolescents. To evaluate the associations between the diet of caregivers and their children, adjusted linear regression models were used. Results: Children and adolescents with T1D intake a diet with a higher total IQD-R score than the non-diabetic sample (p<0.001), and consumed more fruits (p=0.02) and vegetables (p=0.02). There was no difference in any of the IQD- R food groups among caregivers of children and adolescents with and without T1D. In the regression analysis it was found that the quality of the diet of the caregivers of the diabetes group was associated with that of their children (r2=0.09), whereas for the group without diabetes such association was not found (p=0.22). We found a significant effect of T1D on the diet of children and adolescents, while for caregivers this was not confirmed. Conclusion: The quality of the caregivers' diet is associated with the feeding of children and adolescents with T1D.